2018
DOI: 10.1089/rej.2017.2009
|View full text |Cite
|
Sign up to set email alerts
|

Functional Drink Containing the Extracts of Purple Corn Cob and Pandan Leaves, the Novel Cognitive Enhancer, Increases Spatial Memory and Hippocampal Neuron Density Through the Improvement of Extracellular Signal Regulated Protein Kinase Expression, Cholinergic Function, and Oxidative Status in Ovariectomized Rats

Abstract: Due to requirement of novel memory enhancer for menopausal women, this study aimed to determine safety and effect of the functional drink containing the extracts of purple corn cob and pandan leaves (PCP) on memory and brain changes in experimental menopause induced by bilateral ovariectomy (OVX). Acute toxicity of PCP was carried out in female Wistar rats. The results showed that LD50 was more than 2000 mg/kg BW. To determine the cognitive enhancing effect of PCP, OVX rats were orally treated with PCP at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…In addition, 1 mg/ml cob extract was able to activate GR activity. These results agreed with those of a previous study in which in vivo antioxidant activity played a critical role in ameliorating diseases, such as diabetes, Opisthorchis viverrini infection and diabetic cataract [14,40,41] .…”
Section: Resultssupporting
confidence: 92%
“…In addition, 1 mg/ml cob extract was able to activate GR activity. These results agreed with those of a previous study in which in vivo antioxidant activity played a critical role in ameliorating diseases, such as diabetes, Opisthorchis viverrini infection and diabetic cataract [14,40,41] .…”
Section: Resultssupporting
confidence: 92%
“…It has been shown that anthocyanin-rich substance can protect against brain damage induced by oxidative stress [12, 5054]. Therefore, the anthocyanin content in the combined extract of O. sativa and A. graveolens may contribute the role on the improvement of brain infarction and dysfunction observed in this study.…”
Section: Discussionmentioning
confidence: 54%
“…MAO activity was measured according to the protocol described previously [ 53 ]. An aliquot of brain homogenate at a volume of 50 μL was incubated with a mixture of 50 μL of chromogenic solution, and 200 μL of 500 μM of tyramine for 30 min at room temperature.…”
Section: Methodsmentioning
confidence: 99%